1995
DOI: 10.1002/zoo.1430140406
|View full text |Cite
|
Sign up to set email alerts
|

Wounding aggression during the formation and maintenance of captive, multimale chimpanzee groups

Abstract: Although the multimale community is the natural social organization of chimpanzees, both wild and captive adult males have killed other adult males and infants in intercommunity conflicts and intragroup aggression. Despite the potential for serious aggression, the formation of captive, multimale social groups is desirable for the efficient, long-term, humane housing of chimpanzees in socially and physically enriched environments and for the education of zoo visitors. The University of Texas Science Park (UTSP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…The SNA techniques in this study could have real implications for future introductions. Chimpanzee introductions are difficult in zoos [Alford et al, 1995;Brent et al, 1997]. Using SNA, an individual could be artificially ''removed'' from its home group, and their subsequent effects on social structure could be predicted, before they physically move between zoos.…”
Section: Sna As a Management Tool For The Edinburgh Zoo Chimpanzee Comentioning
confidence: 99%
“…The SNA techniques in this study could have real implications for future introductions. Chimpanzee introductions are difficult in zoos [Alford et al, 1995;Brent et al, 1997]. Using SNA, an individual could be artificially ''removed'' from its home group, and their subsequent effects on social structure could be predicted, before they physically move between zoos.…”
Section: Sna As a Management Tool For The Edinburgh Zoo Chimpanzee Comentioning
confidence: 99%
“…These records included the results from routine physical examinations as well as all injuries and health problems that required Alford et al [1995], only wounds that required veterinarian intervention were included in the database. Wounds were categorized as severe if they required medical treatment, which included the prescription of antibiotics and/or analgesics, or surgical treatment (i.e.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Attempting to further lower the levels of aggression while approximating wild social conditions is difficult. A number of studies have demonstrated factors that appear to increase aggression in captivity, including: (1) the age and sex of the individual [Alford et al, 1995;Baker et al, 2000], (2) the age and sex composition of the group [Alford et al, 1995], (3) the duration of stable group membership [Bloomsmith et al, 1992;Jensvold et al, 2005], (4) the presence of females with maximally tumescent sexual swellings [Bloomsmith et al, 1992], (5) the level of human activity within the colony [Lambeth et al, 1997;Jensvold et al, 2005], and (6) the presence of unfamiliar humans in the colony [Maki et al, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, each subject contributed a mean of 4.7 years of data to this study. This same wounding database was also used in preparing portions of a previous report [Alford et al, 1995], which can be referred to for more details concerning group formation strategies, subject histories, and wound therapy.…”
Section: Data Collectionmentioning
confidence: 99%
“…Captive chimpanzees probably engage in more aggression than their freeranging counterparts [van Hooff, 1974;Wilson and Wilson, 1968], and a large number of contexts have been identified which may elicit agonistic encounters. These include introductions of unfamiliar animals [Alford et al 1995;Wilson and Wilson, 1968], reunions between familiar animals [Alford et al, 1995;Bygott, 1979;Goodall, 1986;de Waal and Hoekstra, 1980], interventions on behalf of youngsters in conflicts [Goodall, 1986;de Waal and Hoekstra, 1980], redirected aggression resulting from "frustrating" situations [Goodall, 1986;de Waal and Hoekstra, 1980], arousal during feeding [Bloomsmith et al, 1994;Bygott, 1979;Goodall, 1986;Wrangham, 1974], and competition for access to sexually receptive females [Hasegawa et al, 1990;Rumbaugh et al, 1989;de Waal and Hoekstra, 1980].…”
Section: Introductionmentioning
confidence: 99%